Elevation of artemisinin content by co-transformation of artemisinin biosynthetic pathway genes and trichome-specific transcription factors in Artemisia annua - Hassani, Danial; Taheri, Ayat; Fu, Xueqing; Qin, Wei; Hang, Liu; Ma, Yanan; Tang, Kexuan (Frontiers in Plant Science, 2023)
Artemisinin, derived from Artemisia annua, is currently used as the first-line treatment for malaria. However, wild-type plants have a low artemisinin biosynthesis rate. Although yeast engineering and plant synthetic biology have shown promising results, plant genetic engineering is considered the most feasible strategy, but it is also constrained by the stability of progeny development. Here we constructed three independent unique overexpressing vectors harboring three mainstream artemisinin biosynthesis enzymes HMGR, FPS, and DBR2, as well as two trichomes-specific transcription factors AaHD1 and AaORA. The simultaneous co-transformation of these vectors by Agrobacterium resulted in the successful increase of the artemisinin content in T0 transgenic lines by up to 3.2-fold (2.72%) leaf dry weight compared to the control plants. We also investigated the stability of transformation in progeny T1 lines. The results indicated that the transgenic genes were successfully integrated, maintained, and overexpressed in some of the T1 progeny plants’ genomes, potentially increasing the artemisinin content by up to 2.2-fold (2.51%) leaf dry weight. These results indicated that the co-overexpression of multiple enzymatic genes and transcription factors via the constructed vectors provided promising results, which could be used to achieve the ultimate goal of a steady supply of artemisinin at affordable prices around the world.